The Effect of Intra-Arterial Heparin on Neurogenesis in Neurogenic Areas of the Adult Rat Brain: A Narrative Literature Review Based on Ki-67 and Doublecortin Expression - Mohammad Fauzy Saleh; Dwi Rita Anggraini; Andre Marolop Pangihutan Siahaan (Jurnal Ners, 2026)
Abstract Background: Adult neurogenesis—the continuous generation of new neurons in the subgranular zone (SGZ) of the hippocampal dentate gyrus and the subventricular zone (SVZ)—represents a fundamental process of neural plasticity with implications for cognition, memory, and recovery from neurological injury. Heparin, a widely employed anticoagulant, has emerged as a pharmacological agent with pleiotropic effects on the central nervous system, including modulation of growth factor signaling pathways critical to neurogenesis. Objective: This narrative literature review aims to critically synthesize current evidence on the effects of intra-arterial heparin administration on adult neurogenesis, with particular focus on Ki-67 (cellular proliferation) and Doublecortin (DCX; immature neuron migration) as immunohistochemical biomarkers. Methods: A comprehensive search of Scopus, PubMed, ScienceDirect, and Google Scholar databases was conducted using predefined search strings. Studies published between 2015 and 2025 were prioritized, supplemented by seminal foundational works. Fifteen primary articles met inclusion criteria. Results: Converging evidence indicates that heparin exerts neuroproliferative and neuroprotective effects through its interactions with fibroblast growth factor-2 (FGF-2), brain-derived neurotrophic factor (BDNF), and the Wnt/β-catenin and NF-κB signaling pathways. Intra-arterial administration potentiates these effects by restoring microvascular perfusion, thereby facilitating the survival of Ki-67+ progenitor cells and the maturation of DCX+ neuroblasts in neurogenic niches. Conclusion: Intra-arterial heparin demonstrates significant potential as a pro-neurogenic intervention in adult rodent models, supporting its translational investigation in clinical neuropathological conditions. Standardized biomarker protocols combining Ki-67 and DCX immunolabeling are recommended for future preclinical studies. Keywords: adult neurogenesis; heparin; Ki-67; Doublecortin (DCX); neural progenitor cells; subgranular zone; subventricular zone